Mortality in patients with community‐onset pneumonia at low risk of drug‐resistant pathogens: Impact of β‐lactam plus macrolide combination therapy. Issue 5 (14th December 2017) - Okumura, Junya; Shindo, Yuichiro; Takahashi, Kunihiko; Sano, Masahiro; Sugino, Yasuteru; Yagi, Tetsuya; Taniguchi, Hiroyuki; Saka, Hideo; Matsui, Shigeyuki; Hasegawa, Yoshinori; ,
ABSTRACT: Background and objective: Drug‐resistant pathogen (DRP) risk stratification is important for choosing a treatment strategy for community‐onset pneumonia. Evidence for benefits of non‐antipseudomonal β‐lactam plus macrolide combination therapy (BLM) on mortality is limited in patients at low DRP risk. Risk factors for mortality remain to be clarified. Methods: Post hoc analysis using a prospective multicentre study cohort of community‐onset pneumonia was performed to assess 30‐day differences in mortality between non‐antipseudomonal β‐lactam monotherapy (BL) and BLM groups. Logistic regression analysis was performed to assess the therapeutic effect and risk factors for mortality in patients at low DRP risk. Results: In total, 594 patients with community‐onset pneumonia at low DRP risk (369 BL and 225 BLM) were analysed. The 30‐day mortality in BL and BLM was 13.8% and 1.8%, respectively ( P  < 0.001). Multivariate analysis showed that BLM reduced the 30‐day mortality (adjusted odds ratio: 0.28, 95% CI: 0.09–0.87) compared with BL. Independent prognostic factors for 30‐day mortality included arterial partial pressure of carbon dioxide (PaCO2 ) > 50 mm Hg, white blood cell count < 4000/mm 3, non‐ambulatory status, albumin < 3.0 g/dL, haematocrit < 30%, age ≥ 80 years, respiratory rate > 25/min and body temperature < 36°C. Conclusion: In patients with community‐onset pneumonia at low DRP risk, BLM treatment reduced 30‐day mortality compared with BL. Independent risk factors for mortality are potential confounding factors when assessing antibiotic effects in randomized clinical trials. Abstract : See related Editorial Limited studies have been performed to assess antibiotic effects in pneumonia according to drug‐resistant pathogen (DRP) risk. Our results suggest that β‐lactam plus macrolide combination therapy reduces mortality in patients with community‐onset pneumonia at low DRP risk.